Poverty Reduction and Growth Trust-Guidance Note on New Enhanced Safeguards for Debt Sustainability and Capacity to Repay. (Policy Papers; Policy Paper, 2022)
Poverty Reduction and Growth Trust-Guidance Note on New Enhanced Safeguards for Debt Sustainability and Capacity to Repay.